1999
DOI: 10.1001/archsurg.134.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blue Dye and Probe-Assisted Intraoperative Lymphatic Mapping in Melanoma to Identify Sentinel Nodes in 100 Lymphatic Basins

Abstract: To determine whether combining isosulfan blue dye with a radiopharmaceutical agent will increase intraoperative detection of sentinel nodes (SNs) in patients with early-stage melanoma. Patients and Design: Clinical trial with a consecutive sample. Eighty-seven patients with clinical stage I melanoma underwent preoperative lymphoscintigraphy with 1 of 3 radiopharmaceutical agents to identify the lymphatic basin and the site of the SN. All patients subsequently underwent intraoperative lymphatic mapping and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 34 publications
4
66
0
8
Order By: Relevance
“…24,25 When using only PBD, the literature has registered a lower identification rate for the SN (85%) than with GPD (98-100%). [26][27][28][29] Similar data were obtained in our study (PBD = 76% and GPD = 97%). Subgroup analysis of the basins showed that GPD and PBD identified 100% of the inguinal SN.…”
Section: Discussionsupporting
confidence: 90%
“…24,25 When using only PBD, the literature has registered a lower identification rate for the SN (85%) than with GPD (98-100%). [26][27][28][29] Similar data were obtained in our study (PBD = 76% and GPD = 97%). Subgroup analysis of the basins showed that GPD and PBD identified 100% of the inguinal SN.…”
Section: Discussionsupporting
confidence: 90%
“…Given the daily clinical setting, the JCOG0302 trial was basically designed in accordance with the study by Hiratsuka et al [5], i.e., the ICG dye-guided method for open surgery followed by histopathological examination with H&E staining. The dye-guided method is safe, convenient, inexpensive, and widely available in general hospitals, whereas the gamma probe-guided method has issues of legal restriction and the high cost of radioactive substances [10,11]. ICG is a popular, approved, diagnostic reagent [12], and allergic reactions to ICG are fewer than those to blue dyes such as isosulfan blue (Lymphazurin) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The traceability of the sentinel lymph node may be enhanced by immediately preoperative injection of a lymph vessel permeating dye (Patent Blue V) at the tumor site, thus exposing lymphatic pathways and dyeing the sentinel lymph node blue [181,182]. The use of blue dye has been viewed critically by some centers because of the risk for anaphylactic reactions, a permanent tattoo, and the painfulness of the injection [183].…”
Section: Gcpmentioning
confidence: 99%